Genetic parameters of productive traits in guinea pig (Cavia porcellus) of the Saños and Mantaro lines - Julio Cruz, Danny (2022)
The aim of this study was to estimate the variance components, heritability, and genetic and phenotypic correlations of the productive traits of the Saños and Mantaro guinea pig lines, developed at the Santa Ana Agrarian Experimental Station, Junín (Peru). The consanguinity of the two lines was also calculated. Records from 2017 to 2020 were studied. The productive traits of weight at birth (PN), weaning (PD), at week 4 (P4), week 8 (P8) and week 13 (P13) of 1622 and 1874 guinea pigs of the Saños and Mantaro line, respectively were analysed. The estimation of the variance components was carried out using single-character models, while the estimation of genetic and phenotypic correlations was carried out using bivariate models. The fixed effects considered in the model were sex (S), total births (TN), parturition number (NP) and the mother's parturition season (Tp). The animal and litter effect constituted the random components within the model. For PN and PD, the maternal effect was also included as a random component. The mean population consanguinity was 0.67 and 0.18% for the Saños and Mantaro lines, respectively. The heritability of the productive traits was 0.16 ± 0.02 and 0.13 ± 0.03 for PN, 0.18 ± 0.03 and 0.20 ± 0.05 for PD, 0.18 ± 0.04 and 0.14 ± 0.04 for P4, 0.13 ± 0.03 and 0.14 ± 0.03 for P8 and 0.13 ± 0.03 and 0.12 ± 0.03 for P13 for the Saños and Mantaro lines, respectively. Maternal heritability for PN and PD in both lines were less than 0.10. The genetic correlations for the Saños and Mantaro lines were 0.53 ± 0.02 and 0.93 ± 0.06 for PN and PD, 0.85 ± 0.03 and 0.94 ± 0.05 for PD and P4, 0.84 ± 0.03 and 0.74 ± 0.05 for P4 and P8, and 0.83 ± 0.05 and 0.75 ± 0.05 for P8 and P13. The ratio of the variance due to the litter with respect to the phenotypic variance ranged from 49% to 64%, with the contribution in the PD of both lines being greater. Both the heritability and the ratio of the variance due to the litter with respect to the phenotypic variance were similar between both lines of guinea pigs.